Evaluation of the PEΔIII-LC3-KDEL3 Chimeric Protein of Entamoeba histolytica-Lectin as a Vaccine Candidate against Amebic Liver Abscess - Sandra L. Martínez-Hernández; Viridiana M. Becerra-González; Martín H. Muñoz-Ortega; Víctor M. Loera-Muro; Manuel E. Ávila-Blanco; Marina N. Medina-Rosales; Javier Ventura-Juárez (Journal of Immunology Research)
Entamoeba histolytica is an intestinal parasite that causes dysentery and amebic liver abscess. E. histolytica has the capability to invade host tissue by union of virulence factor Gal/GalNAc lectin; this molecule induces an adherence-inhibitory antibody response as well as to protect against amebic liver abscess (ALA). The present work showed the effect of the immunization with PEΔIII-LC3-KDEL3 recombinant protein. In vitro, this candidate vaccine inhibited adherence of E. histolytica trophozoites to HepG2 cell monolayer, avoiding the cytolysis, and in a hamster model, we observed a vaccine-induced protection against the damage to tissue liver and the inhibition of uncontrolled inflammation. PEΔIII-LC3-KDEL3 reduced the expression of TNF-α, IL-1β, and NF-κB in all immunized groups at 4- and 7-day postinfection. The levels of IL-10, FOXP3, and IFN-γ were elevated at 7 days. The immunohistochemistry assay confirmed this result, revealing an elevated quantity of +IFN-γ cells in the liver tissue. ALA formation in hamsters immunized was minimal, and few trophozoites were identified. Hence, immunization with PEΔIII-LC3-KDEL3 herein prevented invasive amebiasis, avoided an acute proinflammatory response, and activated a protective response within a short time. Finally, this recombinant protein induced an increase of serum IgG.